Human platelets display dysregulated sepsis-associated autophagy, induced by altered LC3 protein-protein interaction of the Vici-protein EPG5. Issue 7 (3rd July 2022) - Schwertz, Hansjörg; Rowley, Jesse W.; Portier, Irina; Middleton, Elizabeth A.; Tolley, Neal D.; Campbell, Robert A.; Eustes, Alicia S.; Chen, Karin; Rondina, Matthew T.
ABSTRACT: Platelets mediate central aspects of host responses during sepsis, an acute profoundly systemic inflammatory response due to infection. Macroautophagy/autophagy, which mediates critical aspects of cellular responses during inflammatory conditions, is known to be a functional cellular process in anucleate platelets, and is essential for normal platelet functions. Nevertheless, how sepsis may alter autophagy in platelets has never been established. Using platelets isolated from septic patients and matched healthy controls, we show that during clinical sepsis, the number of autophagosomes is increased in platelets, most likely due to an accumulation of autophagosomes, some containing mitochondria and indicative of mitophagy. Therefore, autophagy induction or early-stage autophagosome formation (as compared to decreased later-stage autophagosome maturation or autophagosome-late endosome/lysosome fusion) is normal or increased. This was consistent with decreased fusion of autophagosomes with lysosomes in platelets. EPG5 (ectopic P-granules autophagy protein 5 homolog), a protein essential for normal autophagy, expression did increase, while protein-protein interactions between EPG5 and MAP1LC3/LC3 (which orchestrate the fusion of autophagosomes and lysosomes) were significantly reduced in platelets during sepsis. Furthermore, data from a megakaryocyte model demonstrate the importance of TLR4 (toll like receptor 4), LPS-dependent signaling for regulating this mechanism. Similar phenotypes were also observed in platelets isolated from a patient with Vici syndrome: an inherited condition caused by a naturally occurring, loss-of-function mutation in EPG5. Together, we provide evidence that autophagic functions are aberrant in platelets during sepsis, due in part to reduced EPG5-LC3 interactions, regulated by TLR4 engagement, and the resultant accumulation of autophagosomes. Abbreviations: ACTB: beta actin; CLP: cecal ligation and puncture; Co-IP: co-immunoprecipitation; DAP: death associated protein; DMSO: dimethyl sulfoxide; EPG5: ectopic P-granules autophagy protein 5 homolog; ECL: enhanced chemiluminescence; HBSS: Hanks' balanced salt solution; HRP: horseradish peroxidase; ICU: intensive care unit; LPS: lipopolysaccharide; LAMP1: lysosomal associated membrane protein 1; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MTOR: mechanistic target of rapamycin kinase; MKs: megakaryocytes; PFA: paraformaldehyde; PBS: phosphate-buffered saline; PLA: proximity ligation assay; pRT-PCR: quantitative real-time polymerase chain reaction; RT: room temperature; SQSTM1/p62: sequestosome 1; SDS-PAGE: sodium dodecyl sulfate-polyacrylamide gel electrophoresis; TLR4: toll like receptor 4; TEM: transmission electron microscopy; WGA: wheat germ agglutinin.